Coursing paths: 15th anniversary of Rev Rene - Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
To contemplate aspects of a journal which experiences what we call “adolescence process” is indeed challenging. We have traveled paths, sometimes easy, sometimes difficult, in which we advocate that if a seed is thrown into fruitful soil, the results certainly will present as productive. This is the case of Rev Rene. To become adolescent is being in the world. It is creating complicity to dream